PSYCHOLOGICAL ASSESSMENT OF 300 MILITARY PILOT STUDENTS, PILOTS AND FLIGHT CREW MEMBERS USING VIENNA TEST SYSTEM - Hoang Phuc Thanh; Phan Van Manh; Nguyen Huu Ben; Nguyen Minh Phuong (Tạp chí Y học Quân sự, 2023)
Purpose: We aimed to to evaluate some psychological characteristics of military pilot students, pilots, and flight crew members by VTS system, at the Institute of Medicine for Air Defense - Air Force. Methods: Cross-sectional description, combined with analysis of psychophysiological criteria by VTS system. Results: - Assessment of cognitive and attention ability (COG): The highest number of correct responses was in the third round pilot student group (63.57 ± 6.84 times), the lowest number of correct responses was in the flight crew member group (49.01 ± 12.68 times); The highest number of incorrect response was in the flight crew member group (19.82 ± 9.81 times), the lowest number of incorrect responses was in the pilot group (16.19 ± 7.41 times). - Assessment of stress tolerance (DT): The highest number of correct responses was in the third round pilot student group (223.54 ± 45.2 times), and the lowest number of correct responses was in the flight crew member group (171.68 ± 49.85 times); The highest number of incorrect responses was in the flight crew member group (16.37 ± 14.92 times), and the lowest number of incorrect responses was in third round pilot student group (25.89 ± 23.36 times). - Evaluation of visual orientation (LVT): The best visual orientation ability was the of military pilot group, followed by the flight crew member group, the lowest was the pilot student group.